Person–Job Fit and Innovation Behavior: Roles of Job Involvement and Career Commitment - Huang, Wenyuan; Yuan, Chuqin; Li, Min (Frontiers in Psychology, 2019)
This study examines the effect of person-job fit on innovation behavior, highlighting the mediating role of job involvement and the moderating role of career commitment in this relationship. We tested our hypotheses using a sample of 474 employees from 30 IT enterprises in China’s Pearl River Delta region. The results reveal that person-job fit influences innovation behavior by enhancing job involvement. In addition, career commitment strengthens the positive influence of person-job fit on both job involvement and innovation behavior. These findings are consistent with person-environment fit theory and identity theory. This research increases understanding of how person-job fit influences innovation behavior via job involvement and career commitment. Implications and managerial practice are also discussed at the end of the research.